Decoupling the Dynamics of Zinc Hydroxide Sulfate Precipitation/Dissolution in Aqueous Zn–MnO2 Batteries by Operando Optical Microscopy: A Missing Piece of the Mechanistic Puzzle (Adv. Energy Mater. 30/2022). Issue 30 (11th August 2022) - Godeffroy, Louis; Aguilar, Ivette; Médard, Jérôme; Larcher, Dominique; Tarascon, Jean‐Marie; Kanoufi, Frédéric
Abstract : Zn–MnO2 Batteries With a high theoretical gravimetric capacity, intrinsic safety, and low cost, aqueous Zn–MnO2 batteries are promising candidates for grid‐scale energy storage. However, the charge storage at the MnO2 electrode remains a mystery, delaying real‐life applications. In article number 2200722, Frédéric Kanoufi and co‐workers shine light on its mechanism using optical microscopy.